The effect of surface preparation on bonding performances of beam strengthened with GFRP plate / Nurul Farraheeda Abdul Rahman - Abdul Rahman, Nurul Farraheeda (2013)
Fiber reinforced polymers (FRP) have been increasingly used over the past few decades in a variety of structures and have become a popular alternative in construction world. It is one of the effective techniques for strengthening and repairing the reinforced concrete (RC) beams under flexural loads. The bond strength is a fundamental aspect of the structural behavior, since the performances of the concrete-reinforcement system depends on the interface. This study focused on the effect of surface preparation on bonding performances of beam strengthened with GFRP plate. Three beams with the dimensions of 1 00 mm x 200 mm x 1500 mm were subjected to four-point flexural loading test. One beam was considered as unstrengthened control beam, the second beam and the third beam were tested under two different surface preparations which are rough (groove) surface and smooth surface. Experimental data on load, deflection, strain and failure modes of each of the beams were obtained and compared based on the GFRP as the strengthening material. The results indicated that rough (groove) surface preparation increased the ultimate strength of FRP strengthened beams compared to the smooth surface and unstrengthened beams.